Exosomes from dental pulp cells attenuate bone loss in mouse experimental periodontitis. (26th November 2021) - Shimizu, Yuta; Takeda‐Kawaguchi, Tomoko; Kuroda, Izumi; Hotta, Yasuaki; Kawasaki, Hideya; Hariyama, Takahiko; Shibata, Toshiyuki; Akao, Yukihiro; Kunisada, Takahiro; Tatsumi, Junichi; Tezuka, Ken‐ichi
Abstract: Background and objective: Exosomes are small vesicles secreted from many cell types. Their biological effects largely depend on their cellular origin and the physiological state of the originating cells. Exosomes secreted by mesenchymal stem cells exert therapeutic effects against multiple diseases and may serve as potential alternatives to stem cell therapies. We previously established and characterized human leukocyte antigen (HLA) haplotype homo (HHH) dental pulp cell (DPC) lines from human wisdom teeth. In this study, we aimed to investigate the effect of local administration of HHH‐DPC exosomes in a mouse model of periodontitis. Methods: Exosomes purified from HHH‐DPCs were subjected to particle size analysis, and expression of exosome markers was confirmed by western blotting. We also confirmed the effect of exosomes on the migration of both HHH‐DPCs and mouse osteoblastic MC3T3‐E1 cells. A mouse experimental periodontitis model was used to evaluate the effect of exosomes in vivo. The morphology of alveolar bone was assessed by micro‐computed tomography (μCT) and histological analysis. The effect of exosomes on osteoclastogenesis was evaluated using a co‐culture system. Results: The exosomes purified from HHH‐DPCs were homogeneous and had a spherical membrane structure. HHH‐DPC exosomes promoted the migration of both human DPCs and mouse osteoblastic cells. The MTT assay showed a positive effect on the proliferation of human DPCs, but not on mouse osteoblastic cells. Treatment with HHH‐DPC exosomes did not alter the differentiation of osteoblastic cells. Imaging with µCT revealed that the exosomes suppressed alveolar bone resorption in the mouse model of periodontitis. Although no change was apparent in the dominance of TRAP‐positive osteoclast‐like cells in decalcified tissue sections upon exosome treatment, HHH‐DPC exosomes significantly suppressed osteoclast formation in vitro. Conclusions: HHH‐DPC exosomes stimulated the migration of human DPCs and mouse osteoblastic cells and effectively attenuated bone loss due to periodontitis.